The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/su11236669
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Knowledge from Big Data for Sustainability: A Comparison of Machine Learning Techniques

Abstract: At present, due to the unavailability of natural resources, society should take the maximum advantage of data, information, and knowledge to achieve sustainability goals. In today’s world condition, the existence of humans is not possible without the essential proliferation of plants. In the photosynthesis procedure, plants use solar energy to convert into chemical energy. This process is responsible for all life on earth, and the main controlling factor for proper plant growth is soil since it holds water, ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, we also chose a quantitative method to compare competing time series analysis approaches by implementing various methods in combination of different cost function, while comparable papers often select promising configurations beforehand without further examination. This rigorous (in-depth) proceeding, however, results in a trade-off so that only a limited number of different algorithms (or rather pathways) could be implemented in the scope of this scientific work, which is admittedly smaller than comparable studies, such as [19,20] produced.…”
Section: Analytical Approachesmentioning
confidence: 99%
“…Furthermore, we also chose a quantitative method to compare competing time series analysis approaches by implementing various methods in combination of different cost function, while comparable papers often select promising configurations beforehand without further examination. This rigorous (in-depth) proceeding, however, results in a trade-off so that only a limited number of different algorithms (or rather pathways) could be implemented in the scope of this scientific work, which is admittedly smaller than comparable studies, such as [19,20] produced.…”
Section: Analytical Approachesmentioning
confidence: 99%
“…They concluded that LS-SVM based on multi-satellite fusion results is a more accurate estimation on retrieving soil moisture than single satellite means single station. Garg, R., et al (2019) extracted big data for the sustainability of soil nutrition composition comparatively analyzed with machine learning techniques as support vector machine (SVM) using the polynomial function, radial basis function (RBF) methods and others.…”
Section: Svm Prediction On Soil Moisturementioning
confidence: 99%
“…It has significantly improved the prediction of soil moisture with short, medium and huge changes in climate, and hazardous crisis such as in disaster mitigated land. Raghu Garg et al (2019) process using with several machines techniques figured out to extract knowledge from big data learning methods for sustainability on plant-related studied. In this research, attempts have using SVM machine learning methods to retrieve global soil moisture, taking the TDS-1 DDM input and the SMOS SMC as reference.…”
Section: Introductionmentioning
confidence: 99%
“…The preprocessing step includes feature elimination, missing data imputation, normalization, and data division. In the importance measurement step, to measure the importance of each feature, the relevancy between each feature and the failure is analyzed using the random forest algorithm [23][24][25][26]. Then, the feature selection and model building steps are conducted iteratively.…”
Section: Introductionmentioning
confidence: 99%